Are we prepared?: An assessment of preservice science teacher educators' beliefs about nature of science - (:unkn) unknown (WILEY, 2006)
Given the important role of science teacher educators in developing science teachers' understandings of nature of science (NOS), this study explores 15 Turkish prospective science teacher educators' beliefs about NOS in the context of teacher education reform in Turkey. A reflection-oriented qualitative approach was adopted in the investigation. Data were collected through two sets of interviews with the participants and analyzed by means of cognitive maps. The analysis of data revealed that most of the participants of the study had inadequate conceptions regarding NOS. The majority of these inadequate conceptions were concentrated under two aspects of NOS: scientific method and the tentative NOS. The participants' inadequate conceptions appeared to be linked to a lack of prior reflection about NOS. The study has implications for the preservice preparation of science teacher educators, teacher education reform, and teacher thinking at both the practical and the policy levels. (c) 2006 Wiley Periodicals, Inc.
Keywords: CONCEPTIONS; KNOWLEDGE; STUDENTS